ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA ABAD 21 DI SEKOLAH DASAR NEGERI BHAYANGKARI - Saraswati, Susi; Hidayat, Sholeh; Pribadi, Reksa Adya; Dewi, Ratna Sari (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum in the 21st century. The research employed a qualitative descriptive method and was conducted at SDN Bhayangkari. The sample included first and fourth grade teachers, as well as the principal of SDN Bhayangkari. Data collection techniques consisted of interviews, observations, and documentation. The data were processed using qualitative data analysis techniques. This research discusses the implementation of the Merdeka Curriculum at SDN Bhayangkari, focusing on preparation, execution, and supporting and inhibiting factors. The results show that teachers participated in training organized by the education office and the school's IHT (In-House Training) program to understand the curriculum concept, particularly differentiated learning. Preparations also involved planning based on the school’s vision, analyzing students’ learning styles, and developing teaching modules. The curriculum was actively implemented in grades I and IV, including P5 activities, student-centered learning, and diverse assessments involving collaboration with parents. Supporting factors included adequate facilities and teacher training, while challenges involved limited technological proficiency and adaptation to new approaches. Overall, the implementation of the Merdeka Curriculum at SDN Bhayangkari has been effective, despite facing some challenges.